Penerapan Pendekatan Sosiolinguistik dalam Pembelajaran Bahasa di Sekolah Menengah - Zulkifli Ardian Saputra (Journal of Language Studies, 2025)
Language education in secondary schools often focuses on grammar and vocabulary, frequently neglecting the social contexts in which language is used. Sociolinguistics, as a discipline that examines language within its social context, offers a powerful framework for enriching language learning. This paper explores the application of a sociolinguistic approach to language instruction in Indonesian secondary schools. Utilizing a qualitative descriptive method supported by literature review and classroom observations, the study identifies various classroom strategies such as role-play, real-life simulations, and community-based language projects that align with sociolinguistic principles. Findings reveal that incorporating sociolinguistic elements into language teaching improves students’ communicative competence, especially in terms of pragmatic awareness and adaptability in diverse social interactions. Students also demonstrated increased motivation and engagement when learning was connected to their real-life experiences. The study concludes that a sociolinguistic approach not only enhances linguistic proficiency but also cultivates learners’ sociocultural awareness, preparing them for effective communication in a multilingual and multicultural society.